The Implementation of Brainstorming Method by EFL Teachers in Improving Students’ Engagement in Speaking Class A Case Study at SMAN 1 Pangalengan - Neng Nisa Anisa Padilah; Aldha Williyan; Utami Rosalina (Tomorrow's Education Journal, 2024)
This study aims to explore how EFL teachers implement brainstorming methods to increase student engagement in speaking classes and how it impacts student engagement. The method used in this research is qualitative method and case study. Utilizing a qualitative case study approach, this research involves observations, interviews, and document analysis to gather data on how brainstorming activities affect student participation and speaking skills. The results of this study show that EFL teachers at SMAN 1 Pangalengan use brainstorming method to increase student engagement in speaking class. The steps include making lesson plans, choosing the type of brainstorming, preparing teaching materials, conditioning the class, dividing groups, brainstorming sessions, and classifying ideas. The types of brainstorming used were round robin, mind mapping, role storming, and brainwriting. The impact was increased participation, confidence, motivation, critical thinking skills, focus, concentration, and English language skills. This method makes learning more varied and dynamic.